The Prevalence of Migraine Headaches in an Anxiety Disorders Clinic Sample - Senaratne, Rhandi (CNS Neurosci Ther, 2010)
The association between migraine and psychiatric disorders has been reported in both clinical and epidemiological studies. The prevalence of psychiatric disorders has been found to be increased among individuals with migraine. Studies assessing migraine in psychiatric patients are limited and the majority of these studies have focused solely on examining patients with major depression. In the present study, we examined the prevalence and characteristics of migraine headache in an anxiety disorders clinic sample in order to better understand the relationship between these commonly associated conditions. We evaluated 206 consecutive outpatients to an Anxiety Disorders Clinic for the prevalence of migraine. The presence of migraine was established using International Headache Society Criteria. Subjects completed a modified self‐report version of the Headache Diagnostic Questionnaire. In order to assess the relationship between migraine and anxiety disorder symptom severity, subjects completed standardized measures of symptom severity. The prevalence of migraine in our anxiety disorder clinic sample was 67%. Anxiety disorder patients with migraine presented with a significantly greater number of comorbid psychiatric disorders than patients without migraine (P= 0.012). The prevalence of migraine was significantly higher in patients with a diagnosis of either panic disorder with agoraphobia (P= 0.048) or major depressive disorder/dysthymia (P= 0.008) compared to other psychiatric disorders. The severity of anxiety disorder symptoms was significantly higher in patients with migraine compared to patients without migraine. This study suggests that there is an increased prevalence of migraine headaches among anxiety disorder patients as compared to the general population. Migraine comorbidity may have important clinical implications, such that the treatment of one condition could potentially ameliorate the development or progression of the other. Further research is required to better understand the nature and implications of the association between migraine and psychiatric disorders.